Effects of rumen-protected long-chain fatty acid supplementation during the finishing phase of beef steers on live performance, carcass characteristics, beef quality, and serum fatty acid profile. Issue 4 (9th August 2019) - Bakker, Christina E; Blair, Amanda D; Grubbs, Judson K; Taylor, Anna R; Brake, Derek W; Long, Nathan M; Underwood, Keith R
Abstract: The effect of a rumen-protected long-chain fatty acid (LCFA) supplement on live performance, meat quality, blood serum fatty acid profile, and predicted carcass composition was evaluated in this study. Angus steer calves ( n = 99) were fed a low energy diet for 77 d prior to finishing. Prior to study initiation, the steers were separated into 12 pens with eight or nine steers per pen. Steers were transitioned from the low energy forage–based diet to a high concentrate diet containing high moisture ear corn, corn silage, dry rolled corn, soybean meal, and a liquid supplement containing monensin across 21 d. Megalac-R (RPFA) was fed to six pens at 2% of the diet dry matter. Control pens (CON; n = 6) received an additional 2% of diet dry matter as dry rolled corn and soybean meal. The final finishing diet net energy for gain (NEg ) was 1.20 and 1.19 mega calories·kg −1 of dry matter (DM) for RPFA and CON treatments, respectively. Steers were weighed every 28 d. Growth performance data including average daily gain (ADG), gain to feed ratio (G:F), and DM intake (DMI) were calculated as both monthly and overall data. After a 147-d finishing phase, steers were transported to a commercial abattoir for slaughter. After a 28-h chilling period, carcass data were obtained by trained personnel. Final live weights were greater ( P = 0.01) for RPFA than CON cattle. Overall ADG and overall G:F was increased ( P = 0.02; P = 0.01, respectively) for RPFA cattle. Ribeye area, backfat thickness, kidney pelvic heart fat, marbling score, and yield grade did not differ ( P > 0.05) between treatments. Predicted percent carcass fat was increased for RPFA cattle ( P = 0.05). Conversely, predicted percent carcass protein ( P = 0.07) and bone ( P = 0.06) tended to be greater for CON cattle. Long-chain fatty acid supplementation during the finishing phase did not increase marbling scores of the steers in this study but did increase final live weight, HCW, and predicted total body fat. These results suggest that RPFA supplementation has the potential to increase adipose tissue development. However, it is likely that animal age during supplementation and duration of supplementation impact the effect RPFAs have on carcass characteristics.